De novo transcriptome analysis of abiotic stress-responsive transcripts of Hevea brasiliensis - Sathik M.B.M; Anantharamanan R; Kuruvilla L; Luke L.P; Sumesh K.V; Thomas M (Molecular Breeding, 2018)
Cultivation of Hevea brasiliensis, which is being expanded to non-traditional regions, is constrained due to the adverse environmental conditions like extreme drought with high light and low humidity during summer and low temperature with high light during winter, prevailing in these regions. Many attempts are being made to develop drought and low temperature tolerant varieties of Hevea brasiliensis by both conventional and modern methods of breeding. For this purpose, identification of candidate genes/markers associated with drought/cold tolerance is essential. In this attempt, transcriptome sequencing was performed in leaf samples of H. brasiliensis exposed to drought as well as cold stresses using Illumina sequencing technology (RNA-Seq) in order to generate functional genomic resource data which might eventually provide details on molecular mechanisms underlying drought/cold responses in H. brasiliensis Annotated transcriptome data of both drought and cold stress-responsive transcripts were analyzed and further validated by quantitative gene expression analyses. The digital gene expression analysis indicated an upregulation of 268 transcripts and downregulation of 566 transcripts under drought stress while 961 and 109 transcripts were found up and down regulated respectively, under cold stress. Quantitative gene expression analysis of selected drought responsive transcripts revealed the association between transcripts such as ferritin, DNA-binding protein, NAC tf and aquaporin with drought tolerance, and ethylene-responsive transcription factor (ERF) with cold tolerance. These results will enrich the available transcriptome data on H. brasiliensis and would enable the discovery of more genes/markers associated with drought or cold tolerance which can be employed in breeding for drought/cold tolerance in H. brasiliensis.
Keywords: Abiotic stress; Drought; Hevea brasiliensis; Low temperature; NGS; Quantitative gene expression; Stress tolerance markers; Transcriptome sequencing